Access to Digital as a Moderating Influence of Parental Role and Balanced Screen Time on Elementary School Children's Digital Literacy Educationally - Suryadi; Victor Maruli Tua L. Tobing; Sri Utami (Postgraduate, University of Mataram, 2025)
This study aims to explore the dynamics of digital literacy of elementary school children in Madura and examine the role of parental involvement, balanced screen time and access to technology and digital literacy outcomes. Using a quantitative approach where data were collected through online and in-person questionnaires distributed to 210 parents of elementary school students in Madura. then analyzed using SEM-PLS version 3.0. This study revealed that parental involvement does not have a positive influence on digital literacy of elementary school children. Given the low economic status of parents, it is difficult to access digital. Balanced screen time was found to influence digital literacy, which emphasizes the importance of managing screen time for educational purposes. Access to technology as a moderator strengthens the impact of parental involvement and balanced screen time on digital literacy. This study contributes to the understanding of digital literacy of primary school children in Madura. The findings provide valuable insights for education stakeholders, emphasizing the need for a comprehensive curriculum, parental engagement, equitable access to technology and customized digital learning platforms. This knowledge can inform policies and practices aimed at improving digital literacy in primary school children's education, promoting a balanced and inclusive educational environment in Indonesia.